Clinical study of risk factors and ultrasonographic correlation of endometrial hyperplasia according to the WHO classification 2014 - Kanthi, Janu Mangala; Sumathy, Sudha; Vasudevan, Anu; Kamalanathandurai, Gokulkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Type 1 endometrial carcinoma is usually preceded by atypical hyperplasia. Nonatypical hyperplasia should be managed conservatively and atypical hyperplasia have to be managed aggressively. So, the diagnosis is crucial for its management. Methods: The study population included women diagnosed with endometrial hyperplasia by histopathology as per WHO classification 2014 from the year January 2015 to February 2020.Women with endometrial polyp diagnosed by transvaginal ultrasonography and histopathology were excluded. Primary objective was to compare the endometrial thickness between the two types of hyperplasia. Secondary objective was to analyses the risk factors of the two types. Results: In multivariate analysis of logistic regression, diabetic women have 1.57 times risk of developing atypia and obese women have 3.12 times risk of developing atypia. Polycystic ovarian disease is having borderline significance for causing atypia. There was significant difference in endometrial thickness between atypical and nonatypical hyperplasia (P=0.040). In premenopausal women, (P=0.069) the thickness difference in atypia is of only borderline significance. Heteroechoic pattern or cystic spaces in the endometrium also didn’t predict atypia. Conclusions: Mean endometrial thickness is significantly different in atypical hyperplasia. Heteroechoic pattern of endometrium do not predict atypia. We need color doppler sonography to gain knowledge about atypia. Obesity and diabetes mellitus are significant risk factors of atypia.